Physico-chemical characterization and in vitro biological study of manganese doped β-tricalcium phosphate-based ceramics for bone regeneration applications - Arpak, Mehmet Can; Daglilar, Sibel; Kalkandelen, Cevriye; Balescu, Liliana-Marinela; Sasmazel, Hilal Turkoglu; Pasuk, Iuliana; Stan, George E.; Durukan, Kagan; Gunduz, Oguzhan (SPRINGER, 2023)
This work evaluates the effects of manganese (Mn) doping on the morpho-structural features, mechanical performance, and in vitro biological response of beta-tricalcium phosphate (beta-TCP) derived bioceramics for bone tissue engineering applications. Five different Mn doping levels (i.e., 0.01%, 0.05%, 0.1%, 0.5%, and 1 wt.%) were investigated, with the beta-TCP-based bioceramics being sintered at four temperatures (i.e., 1000, 1100, 1200, and 1300 degrees C). A densification improvement was induced when using Mn in excess of 0.05 wt.%; the densification remained stationary in the sintering temperature range of 1200 - 1300 degrees C. The structural analyses evidenced that all samples sintered at 1000 and 1100 degrees C were composed of beta-TCP as major phase and hydroxyapatite (HA) as a minor constituent (similar to 4-6 wt.%). At the higher temperatures (1200 and 1300 degrees C), the formation of alpha-TCP was signalled at the expense of both beta-TCP and HA. The Mn doping was evidenced by lattice parameters changes. The evolution of the phase weights is linked to a complex inter-play between the capacity of the compounds to incorporate Mn and the thermal decomposition kinetics. The Mn doping induced a reduction in the mechanical performance (in terms of compressive strength, Vickers hardness and elastic modulus) of the beta-TCP-based ceramics. The metabolic activity and viability of osteoblastic cells (MC3T3-E1) for the ceramics were studied in both powder and compacted pellet form. Ceramics with Mn doping levels lower than 0.1 wt.% yielded a more favorable microenvironment for the osteoblast cells with respect to the undoped beta-TCP. No cytotoxic effects were recorded up to 21 days. The Mn-doped beta-TCPs showed a significant increase (p < 0.01) in alkaline phosphatase activity with respect to pure beta-TCP.
Keywords: Manganese doping; beta-tricalcium phosphate; Physical-chemical properties; Rietveld XRD analysis; Cytocompatibility; CALCIUM; STRENGTH; BIOMATERIALS; SUBSTITUTION; Materials Science